ENGLISH IN INDONESIA - Yusup, Heri (Fakultas Komunikasi, Sastra, dan Bahasa, 2019)
In Indonesia, English lexis often appears on a number of written media displayed for public consumption. Despite the fact that those media contain English lexis, they may not be necessarily aimed at foreign audience. It seems that English lexis is seen as a more representative medium of expression when it comes to announcing particular information to the public. This paper attempts to illustrate that the occurrence of English lexis in the media used by Indonesian people forms a relatively consistent pattern. Data is taken from fashion blogs written by Indonesian teenagers on a female magazine, flyers about upcoming music events performed by Indonesian bands, banners for anti-drugs campaign, and advertisements for marketing children fashion. The study uses Textually-Oriented Discourse Analysis (TODA) suggested by Fairclough (1992). As for the main focus of the discussion, it will be related to the discourse of globalisation (McGrew, 1996; Bathia & Ritchie, 2004; Kuppens, 2010). The result shows that English lexis is very likely to occur when the information in the Indonesian media is related to globally-shared popular culture (GSPC), e.g. fashion, pop music, and anti-drugs campaign. In conclusion, such use of English lexis reflects the presence of a typical mindset among Indonesian, which suggests that English is an ?ideal? language to represent popular culture.